LITERATURE REVIEW: POLA ASUH IBU DENGAN STATUS GIZI PADA BALITA - Mario Zinduka; Metti Verawati; Dian Laila Purwaningroom; Saiful Nurhidayat; Siti Munawaroh (Universitas Muhammadiyah Ponorogo, 2022)
Parenting is one of the factors that are closely related to the growth and development of toddlers. Parenting is related to the family's ability to provide time, attention and support for children which includes, providing food, caring for cleanliness, and giving affection will affect the child's physical, mental and social. Nutritional problems are closely related to food security problems at the household level which involve knowledge and behavior that do not support a healthy lifestyle. The purpose of this study was to carry out a literature study on Mother Parenting with Nutritional Status in Toddlers. This research method uses a literature review. The search process through Google Scholar publications, PubMeds, Science Direct, uses the keywords